Juvenile delinquency : prevention, assessment, and intervention - Heilbrun, Kirk; Goldstein, Naomi E. Sevin; Redding, Richard E. (Oxford University Press, 2005)
1. Introduction, Richard E. Redding, Naomi E. Sevin Goldstein, and Kirk Heilbrun. 2. Risk Factors, Protective Factors, and the Prevention of Antisocial Behavior Among Juveniles, David DeMatteo and Geoffrey Marczyk. 3. School Violence: Fears Versus Facts,, Dewey G. Cornell. 4. Juvenile Offending, Barry Krisberg and Angela M. Wolf. 5. Mental Health Disorders: The Neglected Risk Factor in Juvenile Delinquency, Naomi E. Sevin Goldstein, Oluseyi Olubadewo, Richard E. Redding, and Fran Lexcen. 6. Risk Factors and Intervention Outcomes: Meta-Analyses of Juvenile Offending, Kirk Heilbrun, Ria Lee, and.